INVESTIGATING THE ARTICULATION DISORDER OF THE ARABIC PHONEME /L/: A CASE STUDY IN POST-ISCHEMIC STROKE PATIENT - Nurfitri, Hanifah; Farisi, Mohamad Zaka; Saleh, Nalahuddin (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This research investigates the articulation of the lateral phoneme /l/ in an Arabic speaking post-ischemic stroke patient using acoustic phonetic analysis and Praat software. Speech data were obtained from the patient’s Qur’anic recitation. The Qur’anic recitation was selected because it serves as a controlled phonetic corpus standardized through the rules of tajwīd, ensuring precise and consistent sound production, which makes it highly suitable for acoustic analysis requiring reliable comparison with native-speaker models. The model speaker was Sheikh Mishary Rasyid Al-Afasy. The analysis focused on the production of /l/ in the vocalic contexts /la/, /li/, and /lu/. The analysis of the surrounding vowels /a/, /i/, and /u/ was essential because these vowels provide the coarticulatory environment that directly shapes the articulation of /l/, allowing vowel impairments to explain disruptions in the target phoneme. The vowel /a/ had a certain degree of impairment on the vowel with increased duration and heightened laryngeal tension. The speech parameters that demonstrated /i/ had a reduction in trunk selective control, thus centralising the vowel. Furthermore, production of the vowel /u/, the most devoid of articulation and therefore the most significant impairment, was characterised by reduced precision with respect to the production of the manner of articulation, as well as marked reduction in coordination of the high and low tongue, and the lips. The severity of the impairment was ranked as /lu/, /li/, /la/. The acoustic baseline identified in this study offers a diagnostic basis for developing targeted, step-by-step speech therapy programs for Arabic-speaking post-stroke patients, directly supporting clinical SLP in this demographic.